Reverse Supply Chain Modeling at XYZ Recycling Company - Butar, Maulida Butar (PT FORMOSA CENDEKIA GLOBAL, 2024)
Attention to the reverse supply chain is increasing due to the increasing value of products and technologies at the end of the supply chain as well as the direct impact of new environmental legislation. Design strategies for reverse supply chains remain relatively unexplored and underdeveloped. Meanwhile, measuring supply chain performance has also become important as understanding, collaboration and integration have increased among supply chain members. It also helps companies to target profitable market segments or identify areas for improvement. Reverse supply chains are seen as one way to increase profits for companies. Company XYZ is a company that operates in recycling products from surrounding shops. This paper will focus on measuring reverse supply chain performance at XYZ recycling company. A simple general framework of the company will be presented as well as its mathematical model. This simple general model is considered applicable by small and medium businesses to optimize their reverse supply chain systems